Desenvolvimento e Uso de Realidade Aumentada em Ambiente Escolar - Leticia Paulucci Munhoz (2022)
​​This project focuses on the development and analysis of the implementation of pedagogical material based on Augmented Reality technology and physical objects for the promotion of ludic activities for use in an educational context. For this, the study evaluated techniques and ways to develop a physical and digital material that could explore the possibilities of the conjunction that technology offers. The project focuses on the design, development and application of a minimum viable product, in order to elucidate the relevant issues in each of these phases and thus outline possible paths for other similar educational projects. Traditional contents of the school curriculum can be approached in innovative and highly appealing ways, which was the driver to seek together with educators and students the best themes and strategies to be approached during this project.